الاختيارات الفقهية للإمام البوني من خلال تفسيره للموطّأ من أول كتاب الأقضية إلى آخر كتاب ال رّجم - مناني, أميرة; مناني, شروق (University of Eloued-جامعة الوادي, 2018)
تناكلت مذكرتنا ىذه موضوع "الاختيارات الفقهية للإمام البوني من خلال تفسيره للموطّأ من أول كتاب الأقضية إلى آخر كتاب الرجم"، كاىتممنا بصفوة أكلى بجمع ىذه الاختيارات بؿاكًلنٌ تسهي ى ل دراستًها للباحثنٌ دراسةن فقهيةن مقارنة، فافتتحنا ىذا ابؼوضوع بدقدمة تيعرٌؼ بو كبأسباب اختيارنا لو، كما انتهجنا فيو خطٌة ثنائية، يدرس مبحثها الأكؿ كلٌ ما يتعلٌق بدصطلحات البحث؛ فعرٌفنا بالإما البوني كتفسنًه، كعرٌجنا على ابؼقصود من الاختيارات الفقهية كالفرؽ بينها كبنٌ الترجيح، كأما مبحثها الثاني فكاف ي صلب ابؼوضوع ابؼدركس؛ إذ استخرجنا الاختيارات الفقهية للئما البوني كحاكلنا تصويرىا في إطاور عاٍّ؛ من خلبؿ بررير بؿلٌ ابػلبؼ في ابؼسألة كذًكر رأم الإما البوني كمستنده، بٌٍ أكردنا بؿلو من مشهور ابؼذىب ابؼالكي، كختمناه بدجموعوة من النتائج ابؼتوصٌل إليها من الدراسة،كالتي كاف من أبن ها: مراعاة ي الإما البوني على غرار أئمة ابؼالكية للمقاصد في اختياراتو. – - The Outline Of the project Our Brief project deals with the subject "The juristic choices of EL-IMMAM-EL-BOUNNY through his explaining ELMOUATA from the book of gudgment into the book of the stoning". We have firstly made an importance to grouping these choices trying to facilitate its study to researchers using "the comparing jurisprudence approach". We have had an intoroduction defining the project and why we have choisenito besides we have conducted the research into two breakdowns. The first part deals shiftly with the terms of the project. We defined who EL-IMMAM EL-BONNY is and his commentary. Also we tried to explain what these juristic choices are and what the deference between them and their overbalance is. In other hand the second part we found out those choices of EL-IMMAM-EL-BONNY assaying to unify them into one general framework. To do so we have appointed the several clashes of the issue and mentioning the view of EL-IMMAM-EL-BONNY and his argement. Then we mentiond the famous views of EL-MADHEB(doctrme) EL- MALIKY. Finally we have closed the project by many deduced result. one of the importants. Taking into account the purposes of his choices, like the rest of theMalik scholars.
مذكرة ليسانس
Keywords: الاختيارات الفقهية /الامام البوني /كتاب الاقضية /كتاب الرجم; Options jurisprudentielles / Imam Al-Buni / Livre de jurisprudence / Livre de la lapidation